Relationship Between Hormonal Contraception History and Breast Cancer at RSUD Jenderal Ahmad Yani Metro City - Amadea, Gebby; Widiyanti, Septi; Prasetyowati, Prasetyowati; Fibrila, Firda (ANTHOR: Education and Learning Journal, 2026)
Breast cancer remains a major global health threat, with WHO data from 2022 reporting 2.3 million cases and 670,000 deaths. Breast cancer is caused by uncontrolled cell growth and hormonal factors, and this disease affects physical and emotional conditions. This quantitative study with a case-control design at General Ahmad Yani Metro Hospital aims to determine the relationship between a history of hormonal contraception and breast cancer. This study involved 93 respondents (31 cases and 62 controls) selected through accidental sampling techniques from the Oncology Surgery and Internal Medicine Rooms. The results showed that 83.9% of respondents had a history of hormonal contraception use. Statistical analysis using the chi-square test and Odds Ratio showed a significant association (p-value = 0.036; OR = 8.750), indicating that this history is associated with a significantly higher risk of developing breast cancer. This study concluded that the use of hormonal contraception is associated with an increased risk of breast cancer, so education, early screening, and regular monitoring are needed, especially for long-term hormonal contraception users.